The role of ancestral phenotypic plasticity in evolutionary diversification: population density effects in horned beetles - Casasa, Sofia; Moczek, Armin P. (Animal behaviour, 2018)
Plasticity's role in shaping phenotypic diversification continues to receive considerable attention. One especially debated issue concerns the significance of genetic accommodation in diversification, and the proposed role of ancestrally plastic responses in facilitating or biasing subsequent genetically canalized differentiation among taxa. Here, we investigated whether pre-existing plasticity in response to variation in population density present in the ancestral Mediterranean range of the bull-headed dung beetle Onthophagus taurus may have mediated previously documented rapid canalized divergences among descendent exotic populations that have been subject to dramatically different levels of competition for mates and resources in the field. We focused on two maternal behavioural traits, two life history traits and two morphological traits. We find that (1) Mediterranean O. taurus exhibited plasticity in response to adult densities for four of our six focal traits; (2) in two of those, plastic responses matched the direction of canalized divergences among natural populations; and (3) the presence and direction of plasticity appeared unrelated to trait type. More generally, our results provide partial support for the hypothesis that evolution by genetic accommodation could have contributed to the very early stages of population differentiation in a subset of traits in O. taurus. •The role of plasticity in evolutionary diversification remains controversial.•Onthophagus taurus populations have diverged heritably in diverse traits.•We exposed a population from the ancestral range to different competition levels.•Plasticity was found for 4/6 traits, with 2 in the direction of evolved divergences.•Results suggest ancestral plasticity may facilitate diversification of some traits.